2018
DOI: 10.1038/s41559-018-0476-8
|View full text |Cite
|
Sign up to set email alerts
|

Hologenomic adaptations underlying the evolution of sanguivory in the common vampire bat

Abstract: Adaptation to specialized diets often requires modifications at both genomic and microbiome levels. We applied a hologenomic approach to the common vampire bat (Desmodus rotundus), one of the only three obligate blood-feeding (sanguivorous) mammals, to study the evolution of its complex dietary adaptation. Specifically, we assembled its high-quality reference genome (scaffold N50=26.9 Mb, contig N50=36.6 Kb) and gut metagenome, and compared them against those of insectivorous, frugivorous, and carnivorous bats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
130
4
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(151 citation statements)
references
References 91 publications
8
130
4
2
Order By: Relevance
“…This composition is consistent with previous reports of vampire bat microbiotas (Carrillo-Araujo et al, 2015;Ingala et al, 2018;Phillips et al, 2012). Vampire bats have gut microbiotas that are compositionally distinct from those of other bats, most likely as a result of selective pressures to optimize bacterial metabolism of bloodmeals (Zepeda Mendoza et al, 2018). Indeed, vampire bats share several key hemolytic bacterial symbionts, such as Aeromonas spp., with other blood-feeding animals such as leeches (Muller, Pinus, & Schmidt, 1980), suggesting that hematophagous animal microbiome composition is closely associated with this specialized diet.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This composition is consistent with previous reports of vampire bat microbiotas (Carrillo-Araujo et al, 2015;Ingala et al, 2018;Phillips et al, 2012). Vampire bats have gut microbiotas that are compositionally distinct from those of other bats, most likely as a result of selective pressures to optimize bacterial metabolism of bloodmeals (Zepeda Mendoza et al, 2018). Indeed, vampire bats share several key hemolytic bacterial symbionts, such as Aeromonas spp., with other blood-feeding animals such as leeches (Muller, Pinus, & Schmidt, 1980), suggesting that hematophagous animal microbiome composition is closely associated with this specialized diet.…”
Section: Discussionsupporting
confidence: 91%
“…Future studies using shotgun metagenomic techniques could be used to analyze how the microbiota changes on a gene-by-gene basis in response to habitat quality, which may give more detailed insight to how these changes in vampire bats impact metagenome functions related to immunity. For example, a hologenomic study of vampire bats found that their microbiotas were characterized by an enrichment of potentially protective bacterial genes originating from Amycolatopsis mediterranei, which is known to produce antiviral compounds (Zepeda Mendoza et al, 2018). Expansion of our study (a) across a quantitative fragmentation gradient and (b) using shotgun metagenomic techniques could provide detailed insights into the functional consequences of habitat fragmentation on vampire bat microbiotas.…”
Section: Discussionmentioning
confidence: 89%
“…For OPN1SW, we obtained sequence data for 28 species from the transcriptome data sets. We then supplemented the OPN1SW nucleotide sequences with those extracted from genome data using a combination of blastn and bl2seq on five noctilionoid bat genomes (Artibeus jamaicensis, Desmodus rotundus (Zepeda Mendoza et al, 2018), Lionycteris spurrelli, Macrotus waterhousii, Mormoops blainvillei and Noctilio leporinus) using the Miniopterus natalensis OPN1SW (XM_016213323.1) sequence as a query. The L. spurrelli and M. waterhousii genomes were sequenced by the Rossiter Lab, and the A. jamaicensis, M. blainvillei and N. leporinus genomes were made available by the Broad Institute.…”
Section: Ihc -Photoreceptor Quantificationmentioning
confidence: 99%
“…Opsin gene evolution We used aligned sequences from the transcriptomes of 38 species together 429 with those from six noctilionoid genomes (Zepeda Mendoza et al, 2018) to estimate rates of 430 molecular evolution of visual opsin genes (OPN1SW, OPN1LW, and RHO) in focal bats. First, we 431 tested for divergent selection modes among species that had S-opsin cones, lacked the S-opsin 432 cones but had an intact mRNA sequence, and those that lacked the S-opsin cones but either did 433 not have OPN1SW transcripts or had a pseudogenized OPN1SW sequence (Figure supplement 2) 434 using the Branch Model 2 of codeml in PAML 4.8a (Yang, 2007).…”
mentioning
confidence: 99%
“…Although still poorly studied in bats, the gut microbiota could be another factor related to their high digestion efficiency (Zepeda Mendoza et al. ). Bats have different gut microbial communities depending whether they feed on fruits, nectar, blood, or insects (Phillips et al.…”
Section: Resultsmentioning
confidence: 99%